Modelling the optical properties of semiconducting nanostructures - Buccheri, A (2016)
In this thesis we describe the development of a real-space implementation of the Bethe-Salpeter equation (BSE) and use it in conjunction with a semi-empirical tight-binding model to investigate the optoelectronic properties of colloidal quantum- confined nanostructures. This novel implementation exploits the limited radial extent and small size of the atomic orbital basis to treat finite systems containing up to ∼4000 atoms in a fully many-body framework. In the first part of this thesis our tight-binding model is initially benchmarked on zincblende CdSe nanocrystals, before subsequently being used to investigate the electronic states of zincblende CdSe nanoplatelets as a function of thickness. The band-edge electronic states are found to show minimal variation for a range of thicknesses and the results of our tight-binding model show good agreement with those predicted using a 14-band k·p model for a nanoplatelet of 4 monolayers (ML) in thickness. Optical absorption spectra were also computed in the independent-particle approximation. While the results of the tight-binding model show good agreement with those of the 14-band k·p model in the low-energy region of the spectrum, agreement with experiment was poor. This reflects the need for a many-body treatment of optical absorption in nanoplatelet systems. In the second part of this thesis we apply our tight-binding plus BSE model to study the excitonic properties of CdSe nanocrystals and nanoplatelets. Simulations performed on CdSe nanocrystals examined an approximation of the BSE equivalent to configuration interaction singles (CIS), and found that both the optical gap and the low-energy spectral features were unaffected by the approximation. A comparison of exciton binding energies with those predicted by CIS demonstrates the sensitivity of results to the exact treatment of dielectric screening and the decision of whether or not to screen exchange. Our model predicts optical gaps that are in strong agreement with average experimental data for all but the smallest diameters, but was not able to reproduce low-energy spectral features that were fully consistent with experiment. This was attributed to the absence of the spin-orbit interaction in the model. Simulations performed on CdSe nanoplatelets investigate the optical gaps and exciton binding energies as a function of thickness. Exciton binding energies were found to reach ∼200 meV for the thinnest system, however, optical gaps were slightly overestimated in comparison to experiment. This is attributed to the reduced lateral dimensions used in our simulations and our bulk treatment of dielectric screening. A two-dimensional treatment of dielectric screening is expected to further increase binding energies. Calculations of the excitonic absorption spectrum reproduce the characteristic spectral features observed in experiment, and show strong agreement with the spectra of nanoplatelets, with thicknesses ranging from 3 ML to 5 ML.